2018
DOI: 10.1002/cphc.201800406
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation of Silver Surfaces Drives the Reactivity and the Selectivity in Homo‐Coupling Reactions

Abstract: Original reaction pathways can be explored in the on-surface synthesis approach where small aromatic precursors are confined to the surface of single crystal metals. The bis-indanedione molecule reacted with itself on silver surfaces in different ways, through a Knoevenagel reaction or an oxidative coupling, leading to the formation of a variety of new molecular compounds and covalently-linked 1D or 2D networks. Noteworthy, original reaction products were obtained that cannot be synthesized in traditional solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 69 publications
(92 reference statements)
1
30
0
Order By: Relevance
“…Copyright 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. (b) Adapted with permission from ref (248). Copyright 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Influence Of the Substrate Nature And Symmetrymentioning
confidence: 99%
“…Copyright 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. (b) Adapted with permission from ref (248). Copyright 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Influence Of the Substrate Nature And Symmetrymentioning
confidence: 99%
“…Quite recently, Clair and coworkers have synthesized a series of conjugated compounds on silver surfaces ( 91‐94) from indane1,3‐dione by Knoevenagel condensation reaction or by oxidative coupling (Figure ). These molecules create a new opportunity in organic electronicsas well as in supramolecular chemistry …”
Section: Role Of Truxene System In Photocatalytic Processesmentioning
confidence: 99%
“…The selectivity of reactions can be routinely dictated by the lattice symmetry of the substrate surface, which has been extensively proven by many studies. Kalashnyk et al have also investigated the influence of the substrate symmetry on the reaction selectivity of Knoevenagel and oxidative coupling reactions by using precursor s ‐indacene‐1,3,5,7(2H,6H)‐tetrone . It turns out that Ag(110) is highly selective, Ag(100) is less selective, and Ag(111) is non‐selective toward the oxidative coupling reaction.…”
Section: Controlling Surface Reaction Via Surface Manipulationmentioning
confidence: 99%
“…In addition to the difference in the products, the surface reaction conditions can be different from and tend to be milder than those in traditional wet chemistry. It has been reported that the coupling reaction of s ‐indacene‐1,3,5,7(2H,6H)‐tetrone takes place at a lower temperature on metal surfaces than that in solvents . Moreover, the polymerization of 4,4′‐diethynyl‐1,1′‐biphenyl that involves a two‐step [2 + 2 + 2] cyclization reaction on Au(111) can be performed at a lower temperature than that for the uncatalyzed alkyne cyclotrimerization from the same precursor …”
Section: Introductionmentioning
confidence: 99%